Intangible cultural heritage, cultural landscape, synergy... (The example of the Polish inscription (2021) of the tradition of the colorful carpet for Corpus Christi processions on the World Representative List of Intangible Cultural Heritage) (Research Announcements "Heritage BG", 2025)
Polish nomination file for the Corpus Christi procession is an outstanding example of a document related to the intangible cultural heritage, which takes into account both the creative force of the human factor and the existing natural assets, as actively involved in modelling the integral value of the element, related to identification processes. References:Convention Concerning the Protection of the World Cultural and Natural Heritage, 1972. Art.1. – https://whc.unesco.org/en/conventiontext/Krastev 2009: Cultural Heritage: Education – Science – Preservation, integrated in tourism (Heritage: ESPRIT), ed. Todor Krastev. Varna: LiterNet, 2009.Picard 2002: Picard, Robert G. European cultural heritage (Volume II): a review of policies and practice, ISBN 92-871-4867-8.Velkov 2009: Velkov, Miroslav. Cultural landscapes – a type of integral heritage (Chapter 3.5.). – Cultural Heritage: Education – Science – Preservation, integrated in tourism (Heritage: ESPRIT), ed. Todor Krastev. https://liternet.bg/publish25/m_velkov/kulturnite.htm, © LiterNet Online Publishing House.
Keywords: Intangible cultural heritage; cultural landscape; synergy; nomination file for the Corpus Christi